Komunikasi Efektif Era New Normal: Kajian Terhadap Proses Pembelajaran Di Universitas Islam Negeri Ar-Raniry Banda Aceh - Saadatul Abadiah (Sadida Islamic Communications and Media Studies, 2022)
This thesis is entitled "Effective Communication of the New normal Era (A Study of the Learning Process at the State Islamic University of Ar-Raniry Banda Aceh)". This study describes the effectiveness of communication on the online learning process at UIN Ar-Raniry Banda Aceh. The formulation of the problem in this research is related to how the new normal era effective communication process towards the learning process at UIN Ar-Raniry Banda Aceh and what obstacles faced by students and lecturers during the new normal era effective communication process towards the learning process. The theory used is the SOR model (stimulus, organism, response). To get the desired results, the research method used is through a qualitative approach with analytical descriptive methods. This study provides an overview of the observations obtained from the field and will be explained in words. Meanwhile, to complete the required information, this study used data collection techniques through interviews with 10 lecturers and 14 students as respondents. The results showed that effective communication that took place in the new normal era had not been effectively implemented in the teaching and learning process. This happened because the learning system through the network was relatively new among lecturers and students at UIN Ar-Raniry Banda Aceh. In addition, the lack of self awareness in prioritizing teaching and learning in the online period has made online learning not implemented optimally. Therefore, responding to all the obstacles that hinder the effective communication process for the learning process at UIN Ar-Raniry Banda Aceh, students and lecturers can be more proactive in conducting teaching and learning relationships and work together to support the achievement of effective communication with all existing limitations, so that effective communication in learning in the new normal era can be maximally implemented according to the digital era 4.0.